Human security for humanitarian and development practitioners : the experience of aid workers from New Zealand Red Cross : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Development Studies at Massey University, Palmerston North, New Zealand - Davy, Aaron James (Massey University, 2014)
This thesis aims to investigate the application of human security to informing and reflecting the experience of New Zealand Red Cross (NZRC) aid workers, particularly those delivering health and medical assistance in highly ‘militarised’ locations. It is claimed by some that the roots of human security are actually found in the nineteenth-century establishment of the Red Cross and it’s operational mandate since that time. Contemporary case-studies of NZRC aid worker experience of personal security will assist in elucidating this claim, particularly in reference to the organisation’s record of working in situations of conflict and insecurity, and its association with military frameworks. With its focus upon a broad range of risks to the individual or community, human security may appear as an ambiguous or dissociated framework for the application to a single organisational occupation or individual. Additionally, a broad scan of academic literature suggests that existing human security dialogue retains a focus on the recipients of humanitarian or developmental aid, as opposed to the aid workers themselves. At the core of human security, however, there may be framing elements that can adequately inform and reflect the context and experience of personal security of development and humanitarian aid workers, such as those from the Red Cross. Red Cross aid workers, deployed through the New Zealand Red Cross, are often located in field environments that include some type of military (or informal militia) presence. The coexistence of such militarised influences within a humanitarian operation or development programme can complicate the aid worker’s experience of security. This thesis investigates the basis of these experiences, and uses a human security discourse to review the frameworks application to the personal security of Red Cross aid workers themselves. This will provide an opportunity to analyse how the operational security of the Red Cross as an organisation can be further informed by a human security analysis.
Keywords: Human security; Humanitarian aid workers; Aid worker safety; Red Cross; Aid workers; New Zealand Red Cross